PANCASILA SEBAGAI DASAR KEPEMIMPINAN: ANALISIS KRITERIA CALEG DAN PEJABAT DI INDONESIA - Saragi, Frans Jhonatan; Manurung, Ricardo; Fattah, M. (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to analyze leadership criteria for legislative candidates and officials in Indonesia based on Pancasila values. Indonesia based on the values of Pancasila. The method used in this research is a literature study, by reviewing various sources such as academic literature, scientific publications, and related documents.academic literature, scientific publications, and related documents. Pancasila, as ideology, contains important values that shape the character and integrity of a leader. character and integrity of a leader. This analysis highlights how Pancasila is applied in the formal and legal criteria that candidates and officials must fulfill. candidates and officials. The literature study shows that the values of Pancasila, such as social justice, fair and civilized humanity, and unity of Indonesia, become important references in the selection and assessment process. Indonesia, become important references in the selection and assessment process of leadership. leadership selection and assessment process. In addition, this article discusses the relevance and challenges of applying these values in the current political context. application of these values in the current political contextz The results show that although the values of Pancasila are formally enshrined in various regulations and leadership selection guidelines, there are challenges in consistent application. This article recommends strengthening the understanding and internalization of Pancasila values in political education and the leadership political education and leadership selection processes to ensure the integrity and quality of leaders who in accordance with the aspirations of the nation.